Multilayer interlocked woven fabrics: simulation of RTM mold filling operation with preform permeability properties - Fangueiro, Raúl (2010)
The simulation of resin flow during the resin transfer molding (RTM) process through multilayered textile fabric of known permeability and porosity has been attempted in this study. A simple three-dimensional computational fluid dynamics (CFD) simulation model has been developed and the results of the simulation are compared with the experimental RTM resin flow through multilayer interlocked woven structures. A multiphase simulation model is observed to reasonably predict the time for RTM mold filling. Fabric structural influence in terms of an Interlacement Index (I) has significant influence on the resin flow behaviour of the multilayered preform. A higher I of the preform means a longer time to fill the mold in both the experimental and simulated results. Images of the simulated flow front has been compared with the experimental results and it is observed that not only the mold filling time, but also the area of resin flow in the multilayer perform, is influenced by a fabric structural factor, I.